2010
DOI: 10.1002/mnfr.200900056
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of caffeic and ferulic acid equivalents in plasma after coffee consumption: Small intestine and colon are key sites for coffee metabolism

Abstract: Previous studies on coffee examined absorption of phenolic acids (PA) in the small intestine, but not the contribution of the colon to absorption. Nine healthy volunteers ingested instant soluble coffee ( approximately 335 mg total chlorogenic acids (CGAs)) in water. Blood samples were taken over 12 h, and at 24 h to assess return to baseline. Many previous studies, which used glucuronidase and sulfatase, measured only PA and did not rigorously assess CGAs. To improve this, plasma samples were analyzed after f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
82
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 115 publications
(93 citation statements)
references
References 22 publications
11
82
0
Order By: Relevance
“…18,36,[37][38][39][40] The major CGA metabolites were ferulic, caffeic and isoferulic acid, which were seen in blood stream after CGA, GCE or regular coffee consumption. Physiologically, one-third of ingested CGAs in foods and beverages were absorbed by the small intestine (shown in subjects with ileostomy-a surgical procedure that brings a loop of small intestine, that is, ileum, out onto the surface of the abdominal skin) and was measured by high performance liquid chromatography in the forms of 3-CQA, 4-CQA and 5-CQA in plasma.…”
Section: Metabolites Of Chlorogenic Acid In the Bodymentioning
confidence: 99%
See 1 more Smart Citation
“…18,36,[37][38][39][40] The major CGA metabolites were ferulic, caffeic and isoferulic acid, which were seen in blood stream after CGA, GCE or regular coffee consumption. Physiologically, one-third of ingested CGAs in foods and beverages were absorbed by the small intestine (shown in subjects with ileostomy-a surgical procedure that brings a loop of small intestine, that is, ileum, out onto the surface of the abdominal skin) and was measured by high performance liquid chromatography in the forms of 3-CQA, 4-CQA and 5-CQA in plasma.…”
Section: Metabolites Of Chlorogenic Acid In the Bodymentioning
confidence: 99%
“…Physiologically, one-third of ingested CGAs in foods and beverages were absorbed by the small intestine (shown in subjects with ileostomy-a surgical procedure that brings a loop of small intestine, that is, ileum, out onto the surface of the abdominal skin) and was measured by high performance liquid chromatography in the forms of 3-CQA, 4-CQA and 5-CQA in plasma. 38,39 The remaining two-thirds passed to the large intestine, 1,38 where CGA was further metabolized by gut microflora and then absorbed. Biochemically, the small intestine is the site where cleavage of quinic acid from CQA and FQA, and then the release of caffeic and ferulic acid took place, whereas the colon was important for conversion of both ferulic and caffeic acid to dihydroferulic acid and for its absorption (Figure 1).…”
Section: Metabolites Of Chlorogenic Acid In the Bodymentioning
confidence: 99%
“…62 In comparison, a single serving of espresso coffee provides between 24 -422 mg of CGA and 51 -322 of caffeine, corresponding to approximately 6 -12 mM CGA and 8 -16 mM caffeine depending on the type of roast and the volume consumed. 63 In the studies about the bioavailability of coffee phytochemicals, plasma levels up 1.5 µM CGA and 13 µM methylxanthines have been reported after the intake of coffee beverages providing 2 -4 mM CGA and 1 mM methylxanthines, 19,21,23 with higher plasma concentrations of CGA (up to 10 µM) reported after the intake of roasted coffee. Based on previous results, 40,39 the highest dose tested of phenolic extracts was 100 µg/mL in the present study, corresponded to approximately 200 µM CGA and 50 µM methylxanthines; however, the doses tested for phenolic extracts ≤ 1 µg/mL would be within the physiological range for CGA (equivalent to approximately ≤ 2 µM CGA), while all tested concentrations would be physiological for methylxanthines.…”
Section: Effect On Fibrinogen Bindingmentioning
confidence: 99%
“…57 On the contrary, concentrations of at least 100 µM were necessary to inhibit the expression of TRAP-and ADPinduced P-selectin by the early metabolites CA and FA, and 5-CQA, respectively, 42,58 while the 12 results of this study showed a significant decrease of ADP-induced P-selectin expression at noticeably lower concentrations (20, 10 and 1 µM for CA, FA and 5-CQA, respectively), indicating that the colonic metabolites may have an even stronger effect on platelet function than their phenolic precursors. Early metabolites from CGA appear at 1 -2 h after coffee intake, and have a short life time of approximately 30 min, 21,59 whereas DHCA and DHFA appear in the circulation 5 -10 h after consumption and their life time is between 0.7 and 2.1 h. 19 A longer circulation time of colonic metabolites, together their higher effect on platelet function, suggest that these colonic metabolites may be the main contributors to the beneficial effect of CGA-rich foods on human platelet function. The differences in efficacy could relate to their molecular structure.…”
Section: Effect On Fibrinogen Bindingmentioning
confidence: 99%
See 1 more Smart Citation